2022
DOI: 10.1093/jac/dkac161
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of acquired antifungal drug resistance in principal fungal pathogens and EUCAST guidance for their laboratory detection and clinical implications

Abstract: The increasing incidence and changing epidemiology of invasive fungal infections continue to present many challenges to their effective management. The repertoire of antifungal drugs available for treatment is still limited although there are new antifungals on the horizon. Successful treatment of invasive mycoses is dependent on a mix of pathogen-, host- and antifungal drug-related factors. Laboratories need to be adept at detection of fungal pathogens in clinical samples in order to effectively guide treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 268 publications
2
50
0
1
Order By: Relevance
“…indotineae , and T . rubrum [ 37 ]. Yamada and colleagues introduced the 2 common abovementioned amino acid substitutions into the endogenous SQLE gene of a TRB-sensitive Arthroderma vanbreuseghemii (formerly T .…”
Section: Developments In the Antifungal Susceptibility Testing (Afst)...mentioning
confidence: 99%
See 1 more Smart Citation
“…indotineae , and T . rubrum [ 37 ]. Yamada and colleagues introduced the 2 common abovementioned amino acid substitutions into the endogenous SQLE gene of a TRB-sensitive Arthroderma vanbreuseghemii (formerly T .…”
Section: Developments In the Antifungal Susceptibility Testing (Afst)...mentioning
confidence: 99%
“…The most common substitution in T. indotineae strains reported worldwide is Phe397Leu in 95% of the studies leading to high TRB MICs (range: 1 to >32 mg/L) followed by Leu393Phe (MIC range: 1 to 64 mg/L) and Leu393-Ser (MIC range: 0.5 to 1 mg/L) [3][4][5]7,10,11,[13][14][15][16][17]19,21,22,[25][26][27][28]. Notably, Phe397Leu or Leu393Phe substitutions confer high-level TRB resistance in T. mentagrophytes, T. interdigitale, T. indotineae, and T. rubrum [37]. Yamada and colleagues introduced the 2 common abovementioned amino acid substitutions into the endogenous SQLE gene of a TRB-sensitive Arthroderma vanbreuseghemii (formerly T. mentagrophytes) strain and showed that resistance to TRB in A. vanbreuseghemii transformants was due to the respective point alterations [36].…”
Section: Developments In the Antifungal Susceptibility Testing (Afst)...mentioning
confidence: 99%
“…Notably, ABC transporters have been widely implicated in the development of multidrug resistance (MDR) to antimicrobials or anticancer drugs [ 71 , 72 , 73 ]. MDR conferred by ABC transporters is increasingly concerning in fungal pathogens [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Comprehensive phylogenetic analyses of 27 other fungal species from 18 orders of five fungal phyla defined a complex evolutionary history and classification of fungal ABC transporters [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…51,53 Such mechanisms of antifungal resistance among dermatophytes, yeasts and non-dermatophyte moulds have been reviewed extensively. 10,46,[53][54][55][56][57][58][59] Briefly, azole antifungals (e.g., itraconazole) deplete ergosterol, an essential regulator of fungal cell membrane integrity. 60 Generally, azole resistance among dermatophytes reflects overexpression of genes that regulate membrane transporters, resulting in increased drug efflux from the cell.…”
Section: Microbiological Resistancementioning
confidence: 99%
“…Trichophyton species is mainly conferred by amino acid substitutions in the squalene epoxidase gene that reduce the binding affinity of terbinafine, although increases in drug degradation and efflux transporter expression have also been reported. 10,[56][57][58] As each antifungal drug class tends to provide only one mechanism of action, the…”
Section: Microbiological Resistancementioning
confidence: 99%